Incremental effects of 28 days of beta-alanine supplementation on high-intensity cycling performance and blood lactate in masters female cyclists - Glenn, J. M; Gray, M; Stewart, R; Moyen, N. E; Kavouras, S. A; DiBrezzo, R; Turner, R; Baum, J (Amino acids, 2015)
Within the aging population, there exists a subset of individuals termed masters athletes (MA). As masters-level competition increases in popularity, MA must find methods to enhance individual athletic performance. Longitudinal beta-alanine (BA) supplementation is suggested to enhance physical capability during exercise; however, these effects have not been evaluated in MA. To examine the longitudinal effects of BA on time to exhaustion (TTE), total work completed (TWC), and lactate clearance in female MA cyclists. Twenty-two female MA (age = 53.3 ± 1.0) participated in this double-blind design. Subjects were randomly assigned to BA (n = 11; 800 mg BA + 8 g dextrose) or placebo (PLA; n = 11; 8 g dextrose) groups and supplemented 4 doses/day over 28 days. Every 7 days, subjects completed a cycling TTE at 120 % VO₂ₘₐₓ, and TWC was calculated. Blood lactate was measured at baseline, immediate post, and 20-min post each TTE. No significant differences existed between groups for any variable at baseline (p > 0.05). After 28 days supplementation, BA had greater TTE (23 vs 1 % change) and TWC (21 vs 2 % change) than PLA (p < 0.05). Following the 20-min TTE recovery, lactate was 24 % lower in BA compared to PLA (4.35 vs. 5.76 mmol/L, respectively). No differences existed for variables during intermittent weeks. 28 days of BA supplementation increased cycling performance via an enhanced time to exhaustion and total work completed with associated lactate clearance during passive rest in female MA.